Overview of Solid Waste Management in Kalabahi Regional General Hospital in Alor Regency - Sahbudin Sengaji; Mustakim Sahdan; Johny A. R. Salmun (Universitas Nusa Cendana, 2022)
Hospital waste management is a component of hospital environmental sanitation activities that seek to protect hospital personnel and the community as service recipients from dangers or risk factors for environmental pollution caused by hospital waste such as liquid, solid, and gas waste. This research aims to determine the solid waste management at the Kalabahi Regional General Hospital in Alor Regency in 2020. A descriptive study with a quantitative approach was used as the research method. This research was conducted from August to September 2020. This study's population consists of 7 participants, all of whom are members of the hospital's solid waste management team. The sampling technique in this study uses total sampling. The findings revealed that the hospital had a policy, which is No. 40/RSUD/Kep/01/XI/2015, concerning guidelines for PPI services at the Kalabahi hospital and the decree of the director of the Kalabahi hospital No. 45/RSUD/Kep/01/XII/2015 concerning the management of infectious waste and body fluids, a workforce of 7 individuals (1 SPK and 7 D3), funding from the Budget Implementation Document (DPA), as well as facilities and infrastructure (incinerator, autoclave, trash cans, trolleys, temporary dumping sites, gloves, and masks). The medical waste management process at Kalabahi Hospital starts with sorting and storing, then moves on to transporting, managing, and finally removing hospital medical waste.